Association of Statin Use and Mortality After Transcatheter Aortic Valve Replacement. Issue 8 (16th April 2019) - Peri‐Okonny, Poghni A.; Liu, Yangbo; Malaisrie, S. Chris; Huded, Chetan P.; Kapadia, Samir; Thourani, Vinod H.; Kodali, Susheel K.; Webb, John; McAndrew, Thomas C.; Leon, Martin B.; Cohen, David J.; Arnold, Suzanne V.
Abstract : Background: Statins may reduce mortality after transcatheter aortic valve replacement (TAVR) through prevention of atherosclerotic events or pleiotropic effects. However, the competing mortality risks in TAVR patients may dilute any positive effect of statins. We sought to understand the association of statin use with post‐TAVR mortality. Methods and Results: We included high– or intermediate–surgical risk patients who underwent TAVR as a part of the PARTNER (Placement of Aortic Transcatheter Valves) II and Sapien 3 trials and registries. Outcomes included 2‐year all‐cause, cardiovascular, and noncardiovascular mortality. We used propensity score matching to generate matched pairs between those discharged on a statin and those not on a statin after TAVR. Bias was explored with falsification end points (urinary infection, hip fracture). Among 3956 patients who underwent TAVR, we matched 626 patients on a statin with 626 patients not on a statin at discharge. Among matched patients, statin use was associated with lower risk of all‐cause (hazard ratio [HR] 0.65, 95% CI 0.49‐0.87, P =0.001), cardiovascular (HR 0.66, 95% CI 0.46‐0.96, P =0.030), and noncardiovascular mortality (HR 0.64, 95% CI 0.44‐0.99, P =0.045) compared with no statin use. The survival curves diverged within 3 months and continued to separate over a median follow‐up of 2.1 years. The falsification end points were similar among groups (urinary infection, P =0.66; hip fracture, P =0.64). Conclusions: In an observational, propensity‐matched analysis of TAVR patients, statin use was associated with lower rates of cardiovascular and noncardiovascular mortality compared with no statin use. Given the early emergence of the apparent protective effect of statins, this result may be driven either by pleiotropic effects or by residual confounding despite propensity‐matching methodology.